Being My Own Companion in Times of Social Isolation – A 14-Day Mobile Self-Compassion Intervention Improves Stress Levels and Eating Behavior - Schnepper, Rebekka; Reichenberger, Julia; Blechert, Jens (Frontiers in Psychology, 2020)
The worldwide spread of the coronavirus disease (COVID-19) and the resulting lockdown has affected the whole world and the maintenance of healthy eating behavior might be an additional challenge. Self-compassion interventions emphasize not only treating oneself in a caring way regarding personal weaknesses, e.g. diet lapses, but also the recognition of shared human suffering. Thus, self-compassion might be particularly valuable during the current worldwide crisis due to COVID-19. In this study, participants were randomized to either a 14-day self-compassion intervention arm or a waitlist control arm. The intervention consisted of daily journaling exercises and meditations via smartphone with a focus on improving eating behavior. Before and after the intervention phase, questionnaires on self-compassion, eating, dieting, health behavior, stress, and emotion regulation were completed and body weight was determined. Participants in the treatment arm (n=28) showed an increase in self-compassion, a decrease in perceived stress, eating in response to feeling anxious, and, on trend level, BMI. Changes in self-compassion fully mediated changes in stress. No such effects were found in the waitlist control group (n=29). Thus, self-compassion might help to maintain well-being and healthy eating habits in times of increased stress and isolation. Future studies should replicate these findings outside of the COVID-19 crisis and test the effect of self-compassion in samples with eating disorders or weight problems.